Hypocrite : Moral Legal Criticism of State Officials - Prasetyo, Yogi; Isnandar, Aries; Agiyanto, Ucuk (Kertha Patrika, 2025)
This study examines the hypocritical attitudes of officials in this country from a critical juridical perspective with a moral dimension. The method used in this study is a literature study method with a legal philosophy approach. This study also uses relevant empirical and normative legal data to support the research. The urgency of this research is the increasingly disturbing hypocritical attitudes of officials in this country, which have a negative impact on the life of the nation. Law is an instrument that plays a crucial role in improving this situation. This research differs from previous research that has focused more on the study of cases of violations of positive law by state officials. Meanwhile, this study has a critical dimension through legal morality towards the hypocritical attitudes of officials. The novelty of this research is also evident in the issue of hypocrisy of officials, which is the main topic of study, rather than violations of laws and regulations. The dimension of moral attitudes that is rarely touched by the law becomes a separate and different study in this study.